De-risking private power in Bangladesh: How financing design can stop collusive contracting - Khan, Mushtaq; Watkins, Mitchell; Zahan, Iffat (Elsevier, 2024)
This article was published in The Energy Policy [©2022 Rights managed by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.enpol.2022.113146 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S0301421522003718?via%3Dihub